1997
DOI: 10.1113/jphysiol.1997.sp022016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute changes in oestrogen on muscle function of the first dorsal interosseus muscle in humans.

Abstract: 1. To investigate the effect of the female reproductive hormones on muscle function, patients undergoing in vitro fertilization were tested during two phases of treatment. The first was following the downregulation of pituitary gonadotrophin releasing hormone (GnRH) receptors and the second after 9 days of gonadotrophin injections. 2. Maximal strength and fatiguability of the first dorsal interosseus muscle were assessed when oestrogen and progesterone were low, and less than 2 weeks later when oestrogen produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 11 publications
(14 reference statements)
4
37
1
2
Order By: Relevance
“…Sarwar et al (1996) reported an increase in fatiguability and a slowing of the half-time of relaxation at mid-cycle (day 12-18), but did not measure hormone concentrations. Greeves et al (1997), however, showed no changes with extreme oestrogen fluctuations, which supports the present findings and confirms the suggestion that oestrogen concentration does not affect skeletal muscle fatiguability and contractile properties.…”
Section: A K Janse De Jonge and Others 164supporting
confidence: 82%
See 1 more Smart Citation
“…Sarwar et al (1996) reported an increase in fatiguability and a slowing of the half-time of relaxation at mid-cycle (day 12-18), but did not measure hormone concentrations. Greeves et al (1997), however, showed no changes with extreme oestrogen fluctuations, which supports the present findings and confirms the suggestion that oestrogen concentration does not affect skeletal muscle fatiguability and contractile properties.…”
Section: A K Janse De Jonge and Others 164supporting
confidence: 82%
“…There were no significant differences between menstrual cycle phases for any of the variables. Contrary to the work by Phillips et al (1996) and Sarwar et al (1996), Greeves et al (1997) showed in patients undergoing in vitro fertilization that supra-physiological levels of oestrogen did not cause any changes in strength of the first dorsal interosseus muscle. The present study found no changes in strength over the menstrual cycle and did not show a correlation between oestrogen concentration and strength.…”
Section: A K Janse De Jonge and Others 164contrasting
confidence: 52%
“…A long-term treatment of the developing rat with estrogen reduced the tetanus tension of skeletal muscle [7]. In women, the supplement with a supraphysiological level of estrogen did not affect the contractile force and fatigue process of the first dorsal interosseus muscle [8]. Neither did the administration of estrogen significantly affect the fatigue of the estradiol-injected extensor digitorum longus muscle in rat [9].…”
mentioning
confidence: 93%
“…Researchers used various models of reproductive functioning to investigate this relationship including; the menstrual cycle 6 , the menopause 7 , in vitro fertilisation (IVF) treatment 8 , pregnancy 9 , oral contraceptives 10 (OC's) and hormone replacement therapies 11 (HRT's). Since then, numerous review papers [12][13][14] have been published, yet the number of original research outputs has declined.…”
Section: Introductionmentioning
confidence: 99%